2010
DOI: 10.3174/ajnr.a2080
|View full text |Cite
|
Sign up to set email alerts
|

T2 Relaxation Times Correlated with Stage of Lumbar Intervertebral Disk Degeneration and Patient Age

Abstract: BACKGROUND AND PURPOSE: T2 relaxation times provide a continuous measure of changes in intervertebral disk biochemistry. The purpose of this study was to correlate T2 relaxation times in lumbar disks with patient age and stage of degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
107
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(121 citation statements)
references
References 21 publications
12
107
0
2
Order By: Relevance
“…5: R = 0.97, P \ 0.01). As it has previously been shown that T2 correlate with IVD degeneration [14,16,17], these findings further emphasize the correlation between Dl and IVD degeneration. 117 ±13 89 ±18 52 ±10 38 ±6 P = 0.000* P= 0.000* P = 0.000* P= 0.000* P = 0.004* P= 0.011* P = 0.000* P= 0.001* P = 0.000* P= 0.000* P = 0.000* P= 0.000*…”
Section: Correlation Between Different Histogram Featuressupporting
confidence: 84%
See 1 more Smart Citation
“…5: R = 0.97, P \ 0.01). As it has previously been shown that T2 correlate with IVD degeneration [14,16,17], these findings further emphasize the correlation between Dl and IVD degeneration. 117 ±13 89 ±18 52 ±10 38 ±6 P = 0.000* P= 0.000* P = 0.000* P= 0.000* P = 0.004* P= 0.011* P = 0.000* P= 0.001* P = 0.000* P= 0.000* P = 0.000* P= 0.000*…”
Section: Correlation Between Different Histogram Featuressupporting
confidence: 84%
“…Compared to other studies, similar T2-values of the IVDs were retrieved [14,16,19]. Histogram analysis of IVDs of different Pfirrmann grades generated a wide and continuous range of Dl which shows that histogram analysis might be a suitable tool to be used for objective and continuous IVD degeneration classification.…”
Section: Discussionmentioning
confidence: 56%
“…The most common method in the literature with regard to T1 and T2 is to acquire small regions of interest that are anatomically based. [6][7][8][9] Authors have used standard ROIs, delineating subregions within the intervertebral disk to extract quantitative data specifically from the NP and AF. 6,7 Additional intermediate ROIs on boundaries between the nucleus and annulus have also been used.…”
mentioning
confidence: 99%
“…We consider our method more reliably reproducible than the visual manual selection of ROIs used in previous reports for minimizing measurement bias. 13,15,16 In the IVD, we observed a significant decrease in T 2 values in the DS group for only the anterior AF, which indicated greater degeneration in the DS group. We observed no significant changes in T 2 values in either group for the posterior AF and NP.…”
Section: Discussionmentioning
confidence: 70%
“…11,13 Previous studies have reported decreased T 2 values of the NP with disc degeneration. [13][14][15] Others have reported decreased or increased T 2 values of the AF with degeneration without consensus. 14,16 In addition, the association of T 2 values with FJ and degeneration has not been investigated.…”
Section: Introductionmentioning
confidence: 99%